Preoperative Serum CA-125 Levels in Patients with Ovarian Cancer - CancerDr. Jannatul Ferdous; Dr. Fakhria Alam; Dr. Mohammad Mostafizur Rahman (SSB Global Journal of Medical Science, 2024)
Introduction: A noteworthy proportion of patients with stage I disease have usual preoperative serum levels, and not all cell types rapid the antigen. Our aim of this study was to predict preoperative serum CA-125 levels in patients with ovarian cancer. Material & Methods: This cross-sectional study was carried out at the Department of Gynecological Oncology, Department of Gynae & Obstetric, Ashiyan Medical College Hospital, Barua Khilkhet, Dhaka, Bangladesh during the period from January 2015 to December 2015. A total of 100 patients were selected using purposive sampling technique for this study. Data were collected and documented on a preformed and pretested structured questionnaire. Clinical examination and relevant investigation were done and recorded accordingly. Data were processed and analyzed with the help of computer software SPSS 22. Results: Mean age of the study subjects was 45.7 ± 15.2 years with a range of 13-75 years. Table II shows education status of the study subjects. It was observed that half of the study subjects had education up to primary level, 26% had studied up to secondary level, 19% up to higher secondary level and only 5% were graduate. Mean BMI was 23.3± 3.0 kg/m2, mean age of marriage was 16.1± 2.8years and mean CA-125 level was 547.02± 478.74. Maximum study subjects had stage III (44.0%) followed by stage II (24.0%), stage I (21. 0%) and stage IV (11.0%). Also, most of the study subjects had serous tumors (70.0%) followed by mucinous tumors (11.0%), endometrioid adenocarcinoma (8.0%), clear cell tumors (4.0%), malignant tertoma (5.0%), Brenner (1.0%) and dysgerminoma (1.0%). Endometrioid adenocarcinoma was found in elderly study subjects and clear cell tumor was found in young aged study subjects. Histopathological type according to grading of ovarian tumor describes, all stage IV tumors were serous, all clear cell and Brenner tumors were stage I, and all endometrioid adenocarcinoma tumors were stage III. Serum CA-125 was elevated at the advanced stage of ovarian cancer. Conclusion: Serum CA-125 had significant positive correlation with surgical stage of ovarian cancer in epithelial cancer patients of this study. But in case of germ cell ovarian cancer, it showed a negative correlation